2020
DOI: 10.1007/s00424-020-02370-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NaPi-IIb in rodent and human kidney and upregulation in a model of chronic kidney disease

Abstract: Na + -coupled phosphate cotransporters from the SLC34 and SLC20 families of solute carriers mediate transepithelial transport of inorganic phosphate (Pi). NaPi-IIa/Slc34a1, NaPi-IIc/Slc34a3, and Pit-2/Slc20a2 are all expressed at the apical membrane of renal proximal tubules and therefore contribute to renal Pi reabsorption. Unlike NaPi-IIa and NaPi-IIc, which are rather kidney-specific, NaPi-IIb/Slc34a2 is expressed in several epithelial tissues, including the intestine, lung, testis, and mammary glands. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 77 publications
(118 reference statements)
1
21
0
Order By: Relevance
“…2002) cotransporters, whereas the role of the recently described renal Slc34a2 /NaPi‐IIb remains unclear (Motta et al . 2020). The quantitative role of the Slc20 family in the intestinal and/or renal transcellular transport of P i is probably minor, at least in mice (Pastor‐Arroyo et al .…”
Section: Introductionmentioning
confidence: 99%
“…2002) cotransporters, whereas the role of the recently described renal Slc34a2 /NaPi‐IIb remains unclear (Motta et al . 2020). The quantitative role of the Slc20 family in the intestinal and/or renal transcellular transport of P i is probably minor, at least in mice (Pastor‐Arroyo et al .…”
Section: Introductionmentioning
confidence: 99%
“…NPT2B (SLC34A2) is expressed in the enterocyte brush border membrane, where it is upregulated by calcitriol [ 41 ], and in alveolar type II cells in the lungs. The mRNA expression of NPT2B in human lung is 30-fold higher than in the small intestine [ 42 , 43 ]. NPT2B has also recently been localized in the kidney medullary thick ascending limb in humans, although levels are ~100-fold lower than in lung [ 42 ].…”
Section: Phosphate Transporters: Knowledge From Animal Models and Human Physiologymentioning
confidence: 99%
“…NPT2B has also recently been localized in the kidney medullary thick ascending limb in humans, although levels are ~100-fold lower than in lung [ 42 ]. Whereas it has been shown that renal NPT2B transcripts are upregulated in a mouse model of chronic kidney disease (CKD) [ 43 ], its overall role in normal renal phosphate handling remains unknown. Diseases that have the potential to impact NPT2B function would be expected to cause an imbalance in phosphate homeostasis if this protein plays a critical role in intestinal phosphate absorption.…”
Section: Phosphate Transporters: Knowledge From Animal Models and Human Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is understood about the mechanism of phosphate reabsorption in the distal nephron. Recently, NPT2b has been localized to the apical membrane of the TAL in the kidney, but its purpose requires further investigation (125) . Furthermore, data concerning the effect of aging on phosphate homeostasis are limited.…”
Section: Role Of the Kidney In Phosphate Homeostasismentioning
confidence: 99%